A Literature Review on the Aspects Influencing Earnings Management and its Implications for the Capital Market - Khaerunnisa, Ana; Karfina AR, Lilis Karfina AR; Rasyid, Syarifuddin; Darmawati, Darmawati (International Journal Of Economics Social And Technology (IJEST), 2025)
Earnings management is a practice that affects a company's financial statements and the capital market as a whole, influenced by internal factors such as accounting policies and ownership structure, as well as external factors such as government policies and capital market liberalization. This study aims to examine the various factors that influence earnings management and its impact on the capital market. The method used isSystematic Literature Review (SLR) by analyzing relevant literature published between 2018 and 2024. The results show that better internal controls, such as audit quality and board quality, can reduce unhealthy earnings management practices, while external factors such as economic crises, corporate social responsibility (CSR), and the influence of open capital markets also have a significant impact on earnings management. Although this study provides important insights into earnings management practices, it has limitations as it relies solely on existing literature without direct empirical data from specific companies or capital markets. Furthermore, this study does not consider new factors such as the impact of technology or recent regulatory changes that influence earnings management practices. This study suggests that regulators and companies need to take steps to improve financial reporting transparency and reduce earnings management practices that are detrimental to the capital market.